PENCEGAHAN OVER HEATING MESIN MOBIL HILUX DOUBLE CABIN - Ismael Marjuki; Epriyandi Epriyandi (Politeknik Negeri Ketapang, 2021)
Human needs are increasing in the world of transportation, especially for two-wheeled vehicles or more. In the automotive world, especially cars, there are various kinds of systems that work. These systems work in conjunction with one another so that if one of these systems is damaged, the car will be damaged. such as damage to the cooling system which can cause overheating of the engine. Overheating is the occurrence of excessive heat above the engine's working temperature which is caused by damage to one of the components of the cooling system. The occurrence of overheating in the Hilux double cabin car engine is caused by a lack of coolant, the thermostat is not functioning properly, the radiator cap is leaking, the inlet and outlet hoses are cracked and the water pump is damaged. To avoid damage, preventive maintenance must be carried out.